Effects of Steaming, Microwaving, and Hot-Air Drying on the Physicochemical Properties and Storage Stability of Oat Bran - Xue Bai; Mei-Li Zhang; Yuanyuan Zhang; Jing Zhang; Yakun Zhang; Chen Wang; Ruirui Liu (Journal of Food Quality)
Oat bran is a nutrient-dense, resource-rich byproduct that is produced from oat milling. Oxidative deterioration is the main reason that limits the utilisation of oat bran. Thus, improving the storage stability of oat bran has become an urgent requirement. This study aimed to investigate the inhibition of oat bran deterioration via steaming, microwaving, and hot-air drying treatments and the effects of these methods on oat bran physicochemical properties and storage stability. Results indicated that, after the three heating treatments, the solubility of oat bran increased and the powder fluidity showed no significant change (P<0.05). Steam-treated oat bran demonstrated increased initial gelatinisation temperature, peak temperature, and enthalpy, significantly reduced peak viscosity, trough viscosity, breakdown value, final viscosity, and setback value, and significantly improved thermal stability (P<0.05). During accelerated storage, oat bran samples subjected to the three heat treatments showed increased sensory scores and L∗, a∗, and b∗ values, whereas due to the decrease of lipase activity in oat bran, their fatty acid values and malondialdehyde content increased slowly and were always lower than those of unprocessed oat bran. All three heat treatments could improve the storage stability and the quality deterioration of oat bran during storage due to oil oxidation. Steaming had the most significant effect.